Education On Implementing Service Strategies To Build Trust Among Aid Recipients Among MZW FAI UMJ Students - Idrus, Ali; Sudarman, Daman; Nuryadin, Deni; Ilham, Muhammad Dzaky Faqihuddin; Az-Zahra, Deska Maura (Yayasan Rahmat Islamiyah, 2026)
This community service aims to determine the service strategy in increasing the trust of muzakki and mustahik at Baznas South Tangerang. This service was carried out using the working mechanism method during the implementation of this program, where the team went directly to the field to examine the situation and problems in the environment of MZW FAI UMJ students. Results of service Through the presentation of material on the importance of Islamic religious education in the growth and development of early childhood, this can be done from the smallest things, starting with prayers in all children's activities, with parents setting an example that will become good habits for children.